Comparative study for CO2 and R-134a heat pump tumble dryer – A rational approach. (October 2019) - Sian, Rony A.; Wang, Chi-Chuan
Highlights: Drying performance of CO2 versus R-134a was compared via rationally based modeling. Transient behavior of CO2 over R-134a was studied beyond environmental friendliness. CO2 yielded air and clothes temperatures up to 15 °C and 6 °C higher over R-134a. Increments of 13% and 8% in SMER and COP were achieved by CO2 compared to R-134a. Parametric studies and optimization/control strategies have been provided. Abstract: A comparative study on the performance of CO2 and R-134a for heat pump clothes drying applications is conducted via a rationally based model. The model comprises unique features such as capability of handling transient behaviours of drying process, freedom from extra constraints normally imposed on heat pump drying modelling and accountability for detailed geometry of the major components. Simulations for both R-134a and CO2 system are performed, validated and further compared to experimental data available in literatures with good agreement. In comparison with R-134a, CO2 dryer yields higher drum outlet air and clothes temperatures, up to 15 °C and 6 °C, respectively. Yet, increments of 13% and 8% in specific moisture extraction rate (SMER) and coefficient of performance (COP) result on 15% reduction of drying time. Additionally, although subsequent parametric comparison studies on the transient performance of both systems revealed similar effect on system performance subject to same geometrical/operational parameter variation, the analyses also further confirm solid prevalence of the CO2 system over that of R-134a, in terms of COP, SMER and drying time. Finally, a brief discussion regarding pinch analysis is carried out, revealing further potential optimization for the CO2 system regarding heat exchangers.